MANAGERIAL OWNERSHIP MODERATES MATERIAL FLOW COST ACCOUNTING AND RISK MANAGEMENT WITH FINANCIAL PERFORMANCE - Ika Susanti; Nofryanti; Holiawati (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of material flow cost accounting and risk management on financial performance in companies, with managerial ownership as a moderating variable. This research was conducted on energy and industrial sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The method used is quantitative, utilizing secondary data sourced from company annual reports. From a total of 149 registered companies, 27 companies were selected as samples through purposive sampling techniques, resulting in 135 data points for analysis. The results show that material flow cost accounting has a significant positive influence on financial performance, while risk management does not have a significant effect. Furthermore, managerial ownership significantly moderates the relationship between risk management and financial performance, but not for material flow cost accounting. These findings provide insights for investors and academics regarding factors influencing financial performance and serve as a reference for further research in business and finance.